The Art of Startup Fundraising: Pitching Investors, Negotiating the Deal, and Everything Else Entrepreneurs Need to Know - Alejandro Cremades (Wiley, 2016)
Startup money is moving online, and this guide shows you how it works. The Art of Startup Fundraising takes a fresh look at raising money for startups, with a focus on the changing face of startup finance. New regulations are making the old go-to advice less relevant, as startup money is increasingly moving online. These new waters are all but uncharted—and founders need an accessible guide. This book helps you navigate the online world of startup fundraising with easy-to-follow explanations and expert perspective on the new digital world of finance. You'll find tips and tricks on raising money and investing in startups from early stage to growth stage, and develop a clear strategy based on the new realities surrounding today's startup landscape.